1998
DOI: 10.1089/cbr.1998.13.209
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism of the Spontaneous Remission and Regression of Cancer

Abstract: Some reports of spontaneous remission and regression of cancer are preceded by a severe infection accompanied with a high fever. This paper proposes the mechanism of action of febrile infection in inducing spontaneous remission and regression of cancer and its possible implication in treating cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The mechanism of spontaneous remission is not clear, but apoptosis seems to be a part of it [41]. There are many speculations as to the cause of apoptosis, some believe in immunological factors [42,43], like natural killing activity [44] or antibodies [45], while others speculate on the positive effect of fever [46], thyroid hormone stimulation [47], and surgery [48,49].…”
Section: Spontaneous Remission Of Cancer -A Short Reviewmentioning
confidence: 99%
“…The mechanism of spontaneous remission is not clear, but apoptosis seems to be a part of it [41]. There are many speculations as to the cause of apoptosis, some believe in immunological factors [42,43], like natural killing activity [44] or antibodies [45], while others speculate on the positive effect of fever [46], thyroid hormone stimulation [47], and surgery [48,49].…”
Section: Spontaneous Remission Of Cancer -A Short Reviewmentioning
confidence: 99%
“…The mechanism of spontaneous remission is not clear, but apoptosis seems to be a part of it [27]. There are many speculations as to what causes this apoptosis; some believe in immunological factors [28,29], like natural killing activity [30] or antibodies [31], while other speculate in a positive effect of fever [32], thyroid hormone stimulation [33], and surgery [34,35].…”
Section: Improving Coherence Quality Of Life and Survivalmentioning
confidence: 99%
“…Premalignant lesions of the cervix and the mouth may disappear if irritant factors are removed, and the majority of gastric mucosa‐associated lymphoid tissue lymphomas disappear after Helicobacter pylori eradication 5 . Niakan 6 suggested that infection and fever usually precedes spontaneous remissions and regression of cancer. A severe infection and a high fever can result in three actions taking place.…”
Section: Discussionmentioning
confidence: 99%